Praktik Iddah Bagi Wanita Karir - M. Shinwanuddin (JAS MERAH: Jurnal Hukum dan Ahwal al-Syakhsiyyah, 2022)
In the view of Islamic law, a woman has the obligation of observing "ihdad" during her waiting period (iddah) after being divorced by her husband or due to the death of her husband. She is not allowed to leave the house and must refrain from getting married again until her iddah period is over. It is also obligatory for the woman to observe "ihdad" by refraining from beautifying herself or engaging in activities that may attract the attention of men who are not her husband. A woman who has been widowed is allowed to leave the house during the day and part of the night, but she must not spend the night anywhere except in her own home. On the other hand, a woman who has been divorced, whether through revocable divorce (talak raj'i) or irrevocable divorce (talak bain), is not allowed to leave her house during the entire iddah period, whether day or night. Followers of the Shafi'i school of thought believe that if a woman is widowed, she has two obligations: "ihdad" and remaining in the house. However, this does not mean that the opportunity to leave the house is completely closed according to the Shafi'i school of thought. As explained earlier, even though a woman who has lost her husband or has been divorced is generally not allowed to leave the house, if there is a legitimate reason (uzur syar'i), she is allowed to do so.